CONSTRUCTION OF DIGITAL MEDIA NEWS FILTRATION IN HADITH BASED (STUDY OF THE APPLICATION OF HADITH VALIDITY CRITERIA AS A BENCHMARK FOR NEWS VALIDITY) - Daib Insan Labib, Muhammad Alfreda; Syamsul, Ilham (Proceeding International Seminar of Islamic Studies, 2024)
This article discusses efforts to construct news filtration based on the criteria of hadith narrators according to the ulama. Researchers are interested in studying related themes because it is motivated by the massive emergence of invalid news. This phenomenon then initiated researchers to present this research product. The method used in this research is qualitative with library research model. Meanwhile, the method used in the system processes descriptive-analytic data. Several points contained in this research include, 1). Factors causing the spread of invalid news and their implications. 2). Examples of prevention efforts regarding hoax news based on hadith. 3). Opportunities and challenges in filtering news with the validity criteria of narration. Among the conclusions produced from this research are, 1). One of the causes of the amount of news that is not credible is the appearance buzzer who present because of an interest, not because of neutrality. Apart from that, news seekers who are not credible will produce news that is also not trustworthy. 2). Construction of preventive measures against the spread of hoax news hadith based. 3). This construction offering has its fair share of opportunities and challenges fifty-fifty.